2014
DOI: 10.1111/gcb.12744
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the use of an amphibian colour morph as an indicator of climate change

Abstract: The effects of recent climate changes on earth ecosystems are likely among the most important ecological concerns in human history. Good bioindicators are essential to properly assess the magnitude of these changes. In the last decades, studies have suggested that the morph proportion of the eastern red-backed salamander (Plethodon cinereus), one of the most widely distributed and abundant vertebrate species in forests of eastern North America, could be used as a proxy for monitoring climate changes. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 28 publications
4
45
1
Order By: Relevance
“…Lastly, the P. cinereus color morph may not be a useful indicator in understanding climate tolerances. Our findings lend credence to growing evidence that the polymorphism is not tied to climate (Moore & Ouellet, 2015), but may be maintained by assortative mating (Anthony et al., 2008) or apostatic selection (Fitzpatrick, Shook, & Izally, 2009). Our study suggests that the color morph is an equivocal proxy at best for understanding climate tolerance variability.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Lastly, the P. cinereus color morph may not be a useful indicator in understanding climate tolerances. Our findings lend credence to growing evidence that the polymorphism is not tied to climate (Moore & Ouellet, 2015), but may be maintained by assortative mating (Anthony et al., 2008) or apostatic selection (Fitzpatrick, Shook, & Izally, 2009). Our study suggests that the color morph is an equivocal proxy at best for understanding climate tolerance variability.…”
Section: Discussionsupporting
confidence: 86%
“…Collectively, these studies suggest striped morphs prefer cool‐wet conditions and that lead‐backed morphs can better tolerate warm‐dry conditions. However, these climate–morph relationships have not been consistent (Petruzzi et al., 2006), and recent work has criticized the use of the color polymorphism for understanding climate relationships (Moore & Ouellet, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…However, it seems that the possible role of climate in the distribution of the lead-backed morph has never been unanimously recognized; some doubts still persist in the scientific community about the validity of using this morph as indicator of climatic changes (Angleberger and Chinnici 1975;Pfingsten and Walker 1978;Petruzzi et al 2006;Anthony et al 2008). Based on new discoveries in the northern areas of the species' range and on the largest compilation ever made for this species, Moore and ouellet (2014) demonstrate however that climate and geographic variables do not influence the colour morph proportions in P. cinereus populations. Fitzpatrick et al (2009) mentioned that the most reasonable hypothesis to explain the existence of visual polymorphism across a geographical and phylogenetic range as wide as that of P. cinereus is that selection acts directly on appearance.…”
Section: Colour Morphsmentioning
confidence: 92%
“…Burger (1935) was the first to publish evidence that both morphs could be found in the same brood, which showed that they are of the same species (Highton 1959). Both morphs can be found across the species range, throughout southeastern Canada and the eastern united States (Petranka 1998), but in very different proportions (Moore and ouellet 2014). in some areas, both morphs are abundant, while in others, one or the other is more abundant.…”
Section: Colour Morphsmentioning
confidence: 99%
“…The Eastern Red-backed Salamander, Plethodon cinereus, has a broad geographic distribution in northeastern North America (Petranka 1998;Moore and Ouellet 2015). Like other terrestrial plethodontid salamanders, it plays an important role in forest ecosystems (Hickerson et al 2012;Walton 2013;Semlitsch et al 2014).…”
Section: Introductionmentioning
confidence: 99%